1969
DOI: 10.1021/ja01033a017
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the copper-catalyzed addition of diazoalkanes to olefins. I. Steric effects

Abstract: The homogeneous catalyzed addition of ethyl diazoacetate to olefins utilizing (trialkyl phosphitejcopper-(I) chloride complexes was studied. The systematic changes in the isomeric cyclopropane product distribution as a function of the steric bulk of the ligand on copper proves the intermediacy of a carbene-metal-olefin complex in the irreversible cyclopropane-forming step. The direction of the steric effect afforded information on the stereochemistry of the excited complex. As a model system for general homoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
1

Year Published

1979
1979
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(44 citation statements)
references
References 0 publications
2
41
0
1
Order By: Relevance
“…Cu(II)-complexes are applicable as well, but need to be reduced in-situ since Cu(I) is the active species 70 in carbene reactions. This can be achieved by treatment with DIBAL-H, substituted hydrazines, or the diazo agent itself.…”
Section: Scheme 15mentioning
confidence: 99%
See 1 more Smart Citation
“…Cu(II)-complexes are applicable as well, but need to be reduced in-situ since Cu(I) is the active species 70 in carbene reactions. This can be achieved by treatment with DIBAL-H, substituted hydrazines, or the diazo agent itself.…”
Section: Scheme 15mentioning
confidence: 99%
“…64 was also used as starting material for the total synthesis of paraconic acids, 40 i.e. roccellaric acid (69), 41 nephrosteranic acid (70) and protopraesorediosic acid (71). Methylenolactocin (73) and protolichesterinic acid (72) were accessed in a formal total synthesis.…”
mentioning
confidence: 99%
“…The influence of the olefin is the weakest, while the electronic influence of the transition metal provides the dominant regio-and stereochemical control. Studies with chiral catalysts confirmed (21)(22)(23)(24) that the transition metal is directly involved in the product-forming step. The more stable trans cyclopropanes usually predominate and the stereoselecCan.…”
Section: Discussionmentioning
confidence: 94%
“…Then, the yield of cyclopropanes goes up slowly with the prolonged reaction and the yield of dimers decreases concurrently. In literatures [28] and [29], it is suggested that copper(II) is reduced to the copper with lower valence at the beginning of the reaction (see Scheme 3) and that this copper with lower valence shows Scheme 3. CuO was reduced to copper species with lower valence by a trace amount of N 2 CHR at the beginning of the reaction.…”
Section: Reaction Mechanismmentioning
confidence: 99%
“…CuO was reduced to copper species with lower valence by a trace amount of N 2 CHR at the beginning of the reaction. high activity for cyclopropanation reactions [28,29]. However, almost all the dimers are produced within the first few minutes.…”
Section: Reaction Mechanismmentioning
confidence: 99%